2017
DOI: 10.18178/joaat.4.4.324-330
|View full text |Cite
|
Sign up to set email alerts
|

Market Structure of Beef Cattle Business in Payakumbuh West Sumatera

Abstract: The purpose of this study is to determine the market structure and the barriers to entry and exit of beef cattle market in Payakumbuh. Survey was conducted in Payakumbuh West Sumatra, with total of 106 respondents. The market structure was analyzed using concentration ratio. The results showed that cattle traded value of each actor is varies, the highest is Butcher, middlemen, breeder and trader respectively with total value of Rp 7,217,760,000. The results also showed that the concentration ratio of beef catt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…Slaughterhouses also faced the same barriers with traders but had problems with marketing activity. This result is similar to a study by Yuzaria & Rias (2017), where the major barriers to entry were high investment and marketing value. However, a study conducted in Kenya showed that the barriers to entry beef cattle market also include lack of information on sources of livestock for trade, price setting of the beef cattle, high capital, and poor trade practices (Onduso et al, 2020).…”
Section: Lorenz Curve In Input Intermediate and Output Markets In East Javasupporting
confidence: 88%
“…Slaughterhouses also faced the same barriers with traders but had problems with marketing activity. This result is similar to a study by Yuzaria & Rias (2017), where the major barriers to entry were high investment and marketing value. However, a study conducted in Kenya showed that the barriers to entry beef cattle market also include lack of information on sources of livestock for trade, price setting of the beef cattle, high capital, and poor trade practices (Onduso et al, 2020).…”
Section: Lorenz Curve In Input Intermediate and Output Markets In East Javasupporting
confidence: 88%
“…Under the level of medium concentration, new actors of beef cattle were enabled to enter, though they had difficulty in competing with older actors. Contrastingly, the market structure having a higher concentration of oligopoly was highly tough entered by new marketers [37]. This result of the research was following previous research [24,38], arguing that the market concentration of beef cattle was classified as a higher concentration of oligopoly, so that it tends inefficient.…”
Section: Market Structuresupporting
confidence: 72%
“…The concentration was done by measuring the size of company distribution in the industry. To measure it, there were two (2) ways, such as: a) Ratio concentration (Rc) by the following equation [24,25].…”
Section: Analysis Of the Market Structurementioning
confidence: 99%